Effects of training with nintendo wii on balance and mobility in institutionalized elderly - Moreira, Lara Alves; Faber, Lívia Marcondes; Scheicher, Marcos Eduardo (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: One of the consequences of the institutionalization of the elderly is the increased risk of falls. Games of video games have shown ability to improve balance in the elderly population, but there is no data on their use in institutionalized elderly. Objective: To evaluate the effects of training with Nintendo Wii on static balance and functional mobility in elderly living in Long-Term Care Facilities for Elderly. Methods: Participated in the research 10 institutionalized elderly, who underwent training with Nintendo Wii for eight weeks, twice a week. Functional mobility was assessed by the Timed Up and Go (TUG) test and the static balance by a force platform. Results: Significant improvement in TUG was observed (17.65 ± 4.38s pre-treatment and 15.30 ± 3.70s p= 0.03). There was no significant improvement in the static equilibrium variables, but there was a tendency for improvement. Conclusion: The results demonstrated that the intervention with Nintendo Wii significantly improved the functional mobility, but with no improvement in the static balance in the institutionalized elderly.